Declining mortality rates in children admitted to ICU following HCT. (12th December 2020) - Jensen, Marie Louise Næstholt; Nielsen, Jeppe Sylvest Angaard; Nielsen, Jonas; Lundstrøm, Kaare Engell; Heilmann, Carsten; Ifversen, Marianne
Abstract: We aimed to assess short‐ and long‐term mortality, including factors associated with mortality, for children referred to a pediatric intensive care unit (ICU) at Rigshospitalet, Denmark, following haematopoietic cell transplantation (HCT). Data regarding admission to ICU and mortality following HCT for children below 16 years of age between 2000 and 2017 were retrospectively analyzed. We identified 55 ICU admissions in 39 patients following 46 HCTs. The overall in‐ICU, in‐hospital, 3‐month, and 1‐year mortality rates were 33.3%, 43.6%, 46.2%, and 51.3%, respectively. Patients admitted from 2000 to 2010 had a 3‐month mortality of 63.2% and 1‐year mortality of 68.4%, compared to 30% and 35% ( P = .040 and P = .039) for patients admitted from 2011 to 2017. The main reason for ICU admission was respiratory failure (78.2%). Mechanical ventilation (MV) was associated with a higher long‐term mortality ( P = .044), and use of inotropes or vasopressors was associated with increased mortality at all times (all P > .006). Extracorporeal life support, renal replacement therapy, longer ICU stay, and longer time with MV were not associated with increased mortality. Over the past two decades, mortality was significantly reduced in pediatric HCT patients admitted to the ICU. The cause is probably multifactorial and warrants further studies. Our findings support admissions of critically ill pediatric HCT patients to intensive care with encouraging outcomes of even long‐term admissions.